"Informatory Kulturalne" jako miejskie i wojewódzkie biuletyny informacyjno-artystyczne na Ziemi Lubuskiej (1969-2015) = "Information guides" as municipal and provincial information and art newsletters in the Lubusz Land (1969-2015) - Kalisz, Paweł - red.; Buck, Andrzej - red.; Bartkowiak, Przemysław - red. (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The first cultural information guide in the Lubusz Region appeared in 1969. It was ?Zielonogórski Informator Kulturalny? ("Zielona Góra Cultural Guide") published by the Friends of Zielona Góra Society, which appeared in the city and neighboring districts for eight years (1969-1976). Afterwards, "The Cultural Guide of the Gorzów Region" was published, issued by the Regional Culture Center in the years 1978-1981, covering Gorzów and the region. City and regional information guides, edited by L. Fokszan and dr. A. Buck, were published for almost nine years in the period 1991-1999, under the auspices of "Gazeta Nowa", and, afterwards, Radio Zachód and the Regional Cultural Animation Center in Zielona Góra. The fourth newsletter in the Lubusz Region was "Gorzowski Informator Kulturalny" ("Gorzowski Cultural Information Guide"), published by the Wydawnictwo Artystyczno-Graficzne Arsenał, which appeared in the years 1996-1998. Apart from Zielona Góra and Gorzów, the guides were also printed in Choszczno and Żagań. "Choszczeński Informator Kulturalny?, was published by the Cultural Centre in Choszczno in 1997, and ?Żagański Informator Kulturalny? was published by the Palace of Culture and Sport in 2008. Both appeared for less than a year. Nowadays, only the "Zielona Góra Cultural Guide" comes out, published by the Zielona Góra Cultural Centre since 2008. In total, more than one hundred issues have been published during eight years of its existence.
Keywords: informacja; informator; informator kulturalny; kultura; województwo gorzowskie; województwo zielonogórskie; Ziemia Lubuska; information; cultural informantion guide; culture; Lubusz Land